Efforts to Overcome Barriers in The Application of Digital Learning Media in The Implementation of Merdeka Belajar Curriculum in Primary Schools - Rosyid, Haniifah Alyaa Azmiira; Marmoah, Sri; Adi, Fadhil Purnama (Universitas Sebelas Maret, 2024)
The study aims to describe efforts to overcoming inhibiting factors the application of digital learning media in the implementation of independent curricula in primary schools. This research uses a descriptive qualitative approach to case studies. Research data is obtained through observation of the learning process using digital learning media, interviews with teachers and documentation studies at the time of learning. The results of this study indicate that 1) The digital learning media has been implemented quite well, teachers feel helped by the presence of digital learning medium, in addition to the ease of access also because of its interesting presentation so that the pupils become more focused and interested to follow the learning activities. 2) In the application of digital media in SDN 1 Sambi there are several obstacles including: Lack of teacher ability in exploring various kinds of digital learning media. There is a shortage of digital learning facilities and facilities, and there is a lack of internet access, especially during the rainy season. 3) To solve these problems, appropriate solutions are needed: teachers should improve their ability to use media technology by following training programs outside, such as workshops, spots, or seminars related to the application of digital learning media, whereas on network barriers can be overcome by changing classes, so that the class that is far from the reach of wifi can switch with the class close to the wifi source to get the same facilities.